Evaluation of Eletronic Translation Tools through Quality Parameters - Kučiš, Vlasta (Array, 2012)
In the paper, the difference of translation quality of texts obtained trough traditional reference works and online electronic translation tools (corpus and multilingual terminology database) will be measured in three nain categories: lexical, ortographic and punctuation ; syntactically and stylistically using paired samples t-test.